The microbicidal potential of visible blue light in clinical medicine and public health - Haridas, Devika; Atreya, Chintamani D. (Frontiers in Medicine, 2022)
Visible blue light of wavelengths in the 400-470 nm range has been observed to have microbicidal properties. A widely accepted hypothesis for the mechanism of microbial inactivation by visible blue light is that the light causes photoexcitation of either endogenous (present within the microbe) or, exogenous (present in the biological medium surrounding the microbe) photosensitizers such as porphyrins and flavins, which leads to the release of reactive oxygen species that subsequently manifests microbicidal activity. Some of the factors that have been observed to be associated with enhanced microbicidal action include increased duration of exposure, and either pre- or co-treatment with quinine hydrochloride. In case of bacteria, repetitive exposure to the blue light shows no significant evidence of resistance development. Additionally, visible blue light has exhibited the ability to inactivate fungal and viral pathogens and, multidrug-resistant bacteria as well as bacterial biofilms. Visible blue light has demonstrated efficacy in eliminating foodborne pathogens found on food surfaces and exposed surfaces in the food processing environment as well as in the decontamination of surfaces in the clinical environment to minimize the spread of nosocomial infections. We conclude from reviewing existing literature on the application of the blue light in clinical medicine and public health settings that this microbicidal light is emerging as a safer alternative to conventional ultraviolet light-based technologies in multiple settings. However, further comprehensive studies and thorough understanding of the mechanism of microbicidal action of this light in different scenarios is warranted to determine its place in human health and disease.